Simultaneous enrichment of grape pomace with γ-linolenic acid and carotenoids by solid-state fermentation with Zygomycetes fungi and antioxidant potential of the bioprocessed substrates. (25th April 2020) - Dulf, Francisc Vasile; Vodnar, Dan Cristian; Toşa, Monica Ioana; Dulf, Eva-Henrietta
Highlights: Grape pomace was enriched with γ-linolenic acid and carotenoids by fungal solid-state fermentation. U. isabellina presented higher ability to produce γ-linolenic-rich lipids than A. elegans . A. elegans showed a slightly higher carotenoid productivity than U. isabellina . Antioxidant activity of phenolic extracts increased significantly during SSF with A. elegans . Abstract: Two filamentous fungi ( Actinomucor elegans and Umbelopsis isabellina ), were tested for their ability to enrich white grape pomace simultaneously with both γ-linolenic acid (GLA) and carotenoids through solid-state fermentation (SSF) processes. U. isabellina presented higher ability to produce GLA-rich lipids (composed mainly of neutral fractions) than A. elegans (the 6-th day of SSF: 378.85 mg/100 g of pomace – U. isabellina and 193.36 mg/100 g of pomace– A. elegans ). The amounts of β -carotene and lutein for both SSFs gradually increased until the end of the fermentation processes. The effect of fermentation time on the phenolic content and antioxidant activity of grape pomace was also studied. The SSF with A. elegans increased significantly total phenolic and flavonoid contents and DPPH scavenging activity of grape popmace. These bioprocessed grape pomaces with significant amounts of carotenoids and GLA-rich lipids (>94% nutritionally-valuable polyunsaturated fatty acids at the sn -2 position) could be very attractive for food industry.